2013
DOI: 10.1007/s00401-013-1181-y
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptide repeat protein pathology in C9ORF72 mutation cases: clinico-pathological correlations

Abstract: Hexanucleotide repeat expansion in C9ORF72 is the most common genetic cause of frontotemporal dementia and motor neuron disease. Recently, unconventional non-ATG translation of the expanded hexanucleotide repeat, resulting in the production and aggregation of dipeptide repeat (DPR) proteins (poly-GA, -GR and GP), was identified as a potential pathomechanism of C9ORF72 mutations. Besides accumulation of DPR proteins, the second neuropathological hallmark lesion in C9ORF72 mutation cases is the accumulation of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
358
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 307 publications
(391 citation statements)
references
References 37 publications
30
358
2
1
Order By: Relevance
“…Finally, we note that the calculation of [ 18 F]AV‐1451 BP ND data uses the superior cerebellar gray matter as a reference region, as in our other recent papers 5, 7, 9. Although across most of the genetic and sporadic forms of FTD this region remains unaffected, in previous cases with C9orf72 expansion, cerebellar atrophy and dipeptide aggregation have been described 21. In mitigation of this potential shortcoming, whilst as expected there was cerebellar gray matter atrophy in the present C9orf72, there was no observable elevated cerebellar [ 18 F]AV‐1451 signal in the uncorrected PET BP ND map.…”
Section: Discussionmentioning
confidence: 80%
“…Finally, we note that the calculation of [ 18 F]AV‐1451 BP ND data uses the superior cerebellar gray matter as a reference region, as in our other recent papers 5, 7, 9. Although across most of the genetic and sporadic forms of FTD this region remains unaffected, in previous cases with C9orf72 expansion, cerebellar atrophy and dipeptide aggregation have been described 21. In mitigation of this potential shortcoming, whilst as expected there was cerebellar gray matter atrophy in the present C9orf72, there was no observable elevated cerebellar [ 18 F]AV‐1451 signal in the uncorrected PET BP ND map.…”
Section: Discussionmentioning
confidence: 80%
“…However, more recent studies have frequently reported a significant proportion of C9ORF72 mutation cases to have other patterns of FTLD‐TDP, most often type A [9, 11, 15], and rarely type C [16]. Nonetheless, all cases bearing expansions appear to show a similar and characteristic DPR pathology irrespective of what TDP‐43 histological type may also be present [13, 14]. …”
Section: Introductionmentioning
confidence: 99%
“…However, while this is possible-it remains to be proven, at least in a disease context. In C9 FTLD/ALS the major cell types affected are within the cerebellar cortex (granule cells), hippocampus (dentate gyrus and CA2-4 pyramidal cells), and pyramidal neurons in deeper layers of the cerebral cortex, even the occipital cortex, and various subcortical structures [1,9,39,40]. Nonetheless, the distribution of such DPR-containing cells is at odds with the known distribution of neurodegeneration in FTLD/ALS, which itself maps closely to that of TDP-43 inclusion distribution [39] (see Neumann).…”
mentioning
confidence: 99%
“…In C9 FTLD/ALS the major cell types affected are within the cerebellar cortex (granule cells), hippocampus (dentate gyrus and CA2-4 pyramidal cells), and pyramidal neurons in deeper layers of the cerebral cortex, even the occipital cortex, and various subcortical structures [1,9,39,40]. Nonetheless, the distribution of such DPR-containing cells is at odds with the known distribution of neurodegeneration in FTLD/ALS, which itself maps closely to that of TDP-43 inclusion distribution [39] (see Neumann). Indeed, overlap of DPR and TDP-43 is confined to a few cells in DG, but interestingly it would appear that within such co-localisations DPR is innermost and TDP-43 outermost, suggesting DPR changes might predate, or even predispose to TDP-43 pathology [39].…”
mentioning
confidence: 99%
See 1 more Smart Citation